2008
DOI: 10.1016/j.marenvres.2008.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of sticklebacks (Gasterosteus aculeatus) to cadmium sulfide nanoparticles: Biological effects and the importance of experimental design

Abstract: Effects of nanoparticles on aquatic organisms have been little studied to date and toxicological data are urgently needed for development of regulatory frameworks for these substances. Here, we report the findings of a study exposing sticklebacks to cadmium sulfide (CdS) as bulk material and quantum dots. Fish were exposed for 21 d in a flow through test system to 5, 50 or 500 microg l(-1) CdS nanoparticles (nCdS) coated in thiol terminated methyl polyethylene glycol (MPEG), bulk CdS or MPEG at 500 microg l(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…49 Release of Cd 2+ has been described to initiate lipid peroxidation and disrupt membrane composition, 50 and Li et al 19 have previously suspected intracellular ROS production, GSH depletion, and release of Cd 2+ ions as the main toxic mechanisms in CHL cells exposed to CdS NPs. Other studies using Cd NPs or QDs have also found similar results: ROS production, decrease in the GSH/GSSG ratio, 19,51 and cell viability, 52,53 associated with Cd 2+ release. Our results were also consistent with the effects of Zn 2+ described in the literature, i.e.…”
Section: Discussionsupporting
confidence: 64%
“…49 Release of Cd 2+ has been described to initiate lipid peroxidation and disrupt membrane composition, 50 and Li et al 19 have previously suspected intracellular ROS production, GSH depletion, and release of Cd 2+ ions as the main toxic mechanisms in CHL cells exposed to CdS NPs. Other studies using Cd NPs or QDs have also found similar results: ROS production, decrease in the GSH/GSSG ratio, 19,51 and cell viability, 52,53 associated with Cd 2+ release. Our results were also consistent with the effects of Zn 2+ described in the literature, i.e.…”
Section: Discussionsupporting
confidence: 64%
“…ROS generation and oxidative damages induced by Cd-based QDs were already reported at various trophic levels in the aquatic environment, e.g., in algae Chlamydomonas reinhardtii and Thalassiosira pseudonana (Domingos et al, 2011;Zhang et al, 2013), cnidarians Hydra vulgaris (Ambrosone et al, 2012), ragworms Hediste diversicolor (Buffet et al, 2014b), bivalve molluscs E. complanata, M. galloprovincialis and S. plana (Gagné et al, 2008a;Rocha et al, 2014;2015a;Buffet et al, 2015) and fishes Oncorhynchus mykiss and Gasterosteus aculeatus (Gagné et al, 2008b;Sanders et al, 2008), indicating that the MoA of Cd-based QDs is mainly mediated by ROS production and oxidative stress.…”
Section: Tissue Specific Antioxidant Patternsmentioning
confidence: 88%
“… 85 The livers of sticklebacks ( Gasterosteus aculeatus ) exposed to CdS quantum dots exhibited hepatocellular nuclear pleomorphism. 86 …”
Section: Limitations Of Nanobased Materials and Processes For Water Amentioning
confidence: 99%